KIR specificity and avidity of standard and unusual C1, C2, Bw4, Bw6 and A3/11 amino acid motifs at entire HLA:KIR interface between NK and target cells, the functional and evolutionary classification of HLA class I molecules. (18th June 2019) - Gwozdowicz, Slawomir; Nestorowicz, Klaudia; Graczyk‐Pol, Elzbieta; Szlendak, Urszula; Rogatko‐Koros, Marta; Mika‐Witkowska, Renata; Pawliczak, Daria; Zubala, Marta; Malinowska, Agnieszka; Witkowska, Agnieszka; Nowak, Jacek
Abstract: Natural killer (NK) cells make vital contributions to the immune system and the reproductive system. Notably, NK cells of donor origin can recognize and kill residual leukaemic cells and cure malignant patients in hematopoietic stem cell (HSC) transplant setting. NK cell function is regulated by KIRs that recognize cognate HLA class I molecules on target cells, depending on their amino acid residues. In review, we addressed the question of binding capacity and avidity of HLA class I molecules to different killer cell immunoglobulin‐like receptors (KIRs) depending on all interacting amino acid residues both on HLA and KIR side. We searched PubMed database and analysed available HLA:KIR crystallographic data for amino acid residues in HLA molecules, those physically involved in binding KIRs (termed here the "entire KIR interface"). Within entire KIR interface, we selected five functional sequence motifs (14–19, 66–76, 77–84, 88–92 and 142–151) and classified them according to the conservation of their amino acid sequences among 8, 942 HLA class I molecules. Although some conserved amino acid motifs were shared by different groups of KIR ligands, the HLA motif combinations were exclusive for the ligand groups. In 135 common HLA class I molecules with known HLA:KIR recognition, we found 54 combinations of five motifs in each of the KIR‐binding interfaces (C1, C2, Bw4, A3/11) and conserved non‐KIR‐binding interfaces. Based on the entire KIR interface, this analysis allowed to classify 8, 942 HLA class I molecules into KIR specificity groups. This functional and evolutionary classification of entire KIR interfaces provides a tool for unambiguously predicting HLA:KIR interactions for common and those HLA molecules that have not yet been functionally tested. Considering the entire KIR interface in HLA class I molecules, functional interactions of HLA and KIR can be predicted in immune responses, reproduction and allotransplantation. Further functional studies are needed on the HLA:KIR interaction variations caused by the repertoires of peptides presented by HLA molecules and KIR polymorphisms at allelic level.